THE ROUTLEDGE INTERNATIONAL HANDBOOK OF CHILD AND ADOLESCENT GRIEF IN CONTEMPORARY CONTEXTS - Traher, Carrie; Breen, Lauren J. (Taylor & Francis, 2024)
death, grief, bereavement, youth, childhood, child, adolescence, non-death losses, illness, disability, pandemic, COVID-19, Black Lives Matter, BLM, parents, siblings, climate change, environmental grief, immigration, relocation, sexual exploitation, social media, war, oppression